Virulence in Pectobacterium atrosepticum is regulated by a coincidence circuit involving quorum sensing and the stress alarmone, (p)ppGpp. Issue 3 (30th September 2013) - Bowden, Steven D.; Eyres, Alison; Chung, Jade C. S.; Monson, Rita E.; Thompson, Arthur; Salmond, George P. C.; Spring, David R.; Welch, Martin
Summary: Pectobacterium atrosepticum (Pca) is a Gram‐negative phytopathogen which causes disease by secreting plant cell wall degrading exoenzymes (PCWDEs). Previous studies have shown that PCWDE production is regulated by (i) the inter cellular quorum sensing (QS) signal molecule, 3‐oxo‐hexanoyl‐l ‐homoserine lactone (OHHL), and (ii) the intra cellular 'alarmone', (p)ppGpp, which reports on nutrient limitation. Here we show that these two signals form an integrated coincidence circuit which ensures that metabolically costly PCWDE synthesis does not occur unless the population is simultaneously quorate and nutrient limited. A (p)ppGpp null Δ relA Δ spoT mutant was defective in both OHHL and PCWDE production, and nutritional supplementation of wild type cultures (which suppresses (p)ppGpp production) also suppressed OHHL and PCWDE production. There was a substantial overlap in the transcriptome of a (p)ppGpp deficient relA mutant and of a QS defective expI (OHHL synthase) mutant, especially with regards to virulence‐associated genes. Random transposon mutagenesis revealed that disruption of rsmA was sufficient to restore PCWDE production in the (p)ppGpp null strain. We found that the ratio of RsmA protein to its RNA antagonist, rsmB, was modulated independently by (p)ppGpp and QS. While QS predominantly controlled virulence by modulating RsmA levels, (p)ppGpp exerted regulation through the modulation of the RsmA antagonist, rsmB.